Practical machinery safety - Macdonald, Dave, 1942- (Practical professional books from Elsevier., 2004)
Practical Machinery Safety aims to provide you with the knowledge to tackle machinery safety control problems at a practical level whilst achieving compliance with national and international standards. The book highlights the major international standards that are used to support compliance with EU regulations and uses these standards as a basis for the design procedures. It looks at the risk assessment processes used to identify hazards and to quantify the risks inherent in a machine. It introduces the concepts of safety categories as defined by standard EN954-1 (Safety of Machinery) and illustrates the principles of failsafe design, fault tolerance and self-testing. It also provides an introduction to machinery protection devices such as guards, enclosures with interlocks and guard-monitoring relays, locking systems, safety mats, photo-electric and electro-sensitive principles and the application of light curtains, a study of Safety Control System techniques, and introduces the principles of safety-certified PLCs. 1. Plan and implement safety systems that deliver a safe working environment and compliance with national and international standards. 2. Apply simple risk assessments and hazard design methods to your own projects 3. Identify hazards that occur with machinery and know how to deal with them.